Age-dependent blood pressure elevation is due to increased vascular smooth muscle tone mediated by G-protein signalling. (4th November 2015) - Wirth, Angela; Wang, Shengpeng; Takefuji, Mikito; Tang, Cong; Althoff, Till F.; Schweda, Frank; Wettschureck, Nina; Offermanns, Stefan
Abstract: Aims: Arterial hypertension is a major risk factor for cardiovascular diseases. The kidney and its natriuretic function are in the centre of the prevailing models to explain the pathogenesis of hypertension; however, the mechanisms underlying blood pressure elevation remain unclear in most patients. Development of hypertension is strongly correlated with age, and this blood pressure increase typically accelerates in the fourth decade of life. The cause of age-dependent blood pressure elevation is poorly understood. This study aims to understand the role of procontractile G-protein-mediated signalling pathways in vascular smooth muscle in age-dependent hypertension. Methods and results: Similar to humans at mid-life, we observed in 1-year-old mice elevated blood pressure levels without any evidence for increased vessel stiffness, impaired renal function, or endocrine abnormalities. Hypertensive aged mice showed signs of endothelial dysfunction and had an increased vascular formation of reactive oxygen species (ROS) and elevated endothelial ET-1 expression. Age-dependent hypertension could be normalized by ETA receptor blockade, smooth muscle-specific inactivation of the gene encoding the ETA receptor, as well as by acute disruption of downstream signalling via induction of smooth muscle-specific Gα12 /Gα13, Gαq /Gα11, or LARG deficiency using tamoxifen-inducible smooth muscle-specific conditional mouse knock-out models. Induction of smooth muscle-specific ETA receptor deficiency normalized the blood pressure in aged mice despite the continuous presence of signs of endothelial dysfunction. Conclusion: Age-dependent blood pressure elevation is due to a highly reversible activation of procontractile signalling in vascular smooth muscle cells indicating that increased vascular tone can be a primary factor in the development of hypertension.